Chemistry at High Dilution: Dinuclear 99 mTc Complexes. Issue 29 (30th April 2019) - Bolliger, Robin; Frei, Angelo; Braband, Henrik; Meola, Giuseppe; Spingler, Bernhard; Alberto, Roger
Abstract: The formation of di‐ or polynuclear complexes at nanomolar concentrations is generally too slow to be observed with 99m Tc. It is reported in this communication that an appropriate choice of potentially bridging ligands, herein thiols HS‐R, accelerates the dimerization reaction to an extent that dinuclear complexes are formed at very high dilution. The dinuclear nature of [ 99m Tc2 (μ2 ‐SR)3 (CO)6 ] − is shown by chromatographic comparison, not only with its rhenium homologue as commonly done, but also with the true 99 Tc analogue. Abstract : Radioisotopes : Di‐ or multinuclear complexes with radionuclides at high dilution were believed not to exist since concentrations are typically in the nanomolar range. The existence of dinuclear 99m Tc‐complexes formed at high dilution with thiols as bridging ligands has now been assessed